Starejša sodna praksa Sodišča EU o svobodi ustanavljanja - Prostor, Jerneja (Podjetje in delo, 2018)
The article discusses the case law of the Court of Justice on the freedom of establishment, from the Segers case of 1986 to the Cadbury Schweppes case of 2006. A number of decisions, together with the relevant provisions of the Treaty on the Functioning of the European Union, form the legal framework for the setting-up of companies, their cross-border business activities and conversions in the territory of another Member State. The reason for the review of the main conclusions of individual judgments is the latter judgment on the freedom of establishment, i.e. in the Polbud case of October 2017. It will be dealt with in one of the next issues of this publication, together with the Cartesio case, the National Grid Indus case and the VALE case.
Keywords: čezmejna združitev; čezmejni prenos dejanskega sedeža družbe; dejanski sedež družbe; omejitev svobode ustanavljanja; svoboda ustanavljanja